Trophic interactions between two medium-sized mammals: the case of the native Dolichotis patagonum and the exotic Lepus europaeus in a hyper-arid ecosystem. - Reus, Maria Laura (2013)
As medium-sized herbivores, the exotic Lepus europaeus (European hare) and the native Dolichotis patagonum (mara) have been considered ecological equivalents. These species coexist in Ischigualasto Provincial Park, a hyperarid ecosystem with scarce food resources. Our objective was to evaluate diet composition, relationship between diets and food availability, and trophic relationships between both herbivores. Collection of feces and vegetation sampling were made in the Mesquite woodland community. Diet composition was analyzed by microhistological analysis of feces. In both seasons, shrub species represented the most abundant cover type in the area, and annual forbs and grasses appeared in the wet season. Herbivores showed similar dietary ecology: shrubs were the main food items along the year, showing a higher plasticity compared to their diets in other ecosystems, where they selected mostly grasses. The mara selected shrubs such as Atriplex sp. and Prosopis torquata, whereas the European hare selected Cyclolepis genistoides, Atriplex sp., and Bulnesia retama. During the wet season, both herbivores supplemented their diets with grasses and annual forbs. In the dry season, there was increased consumption of cacti, such as Tephrocactus sp. The mara and the European hare are likely close ecological equivalents, in terms of dietary similarity, and they showed strong dietary overlap across the dry season (over 60 %). Thus, we can assume the existence of a potential trophic competition between mara and European hare, especially during the season when food resources are scarce. These results can be important for the management of drylands in South America, where populations of threatened herbivorous species, such as the mara, coexist with exotic animals, sharing spatial and trophic resources even in protected areas.